PERSENTASE RENDEMEN DAN SIFAT SENSORIS NATA DE CASSAVA DENGAN LAMA FERMENTASI DAN PENAMBAHAN EKSTRAK KECAMBAH KACANG HIJAU YANG BERBEDA - Aan Sofyan; Ega Mukti Wandani (UHAMKA PRESS, 2022)
Nata is a food product that is widely known by the public, but nata is commonly made using coconut water which is fermented by the bacterium Acetobacter xylinum. It needs to be a diversification process of making nata by utilizing other substrates, namely cassava extract. This study aims to determine the effect of fermentation time and the addition of mung bean sprout extract on the yield, as well as the sensory properties of nata de cassava. The research method used is experimental research with a research design in the form of a completely randomized design (CRD). There were two types of treatment in this study, namely variations in fermentation time of 9, 11, and 13 days, and variations in the addition of mung bean extract sprout of 0.75%, 1%, and 1.25%. The results showed that the highest yield was 86.2% in the 9-day fermentation treatment with the addition of 0.75% mung bean extract, while the lowest yield was 12.1% at the 13-day fermentation time with the addition of mung bean sprout extract 1. 25%. The best sensory properties of nata de cassava as a whole were at 11 days of fermentation with the addition of 1% mung bean sprout extract. This study concludes that there is no effect of fermentation time and the addition of different green bean sprout extracts on the nata de cassava yield.